Mecanismos alternativos de solución de conflictos para el posconflicto en la organización - Fajardo Colmenares, Alexandra Catalina
Conflict resolution is a daily mechanism and for more than two decades has been gaining relevance within organizations in the world, in Colombia just a decade ago, since the academy began to include such topics resilience, Organizational climate and assertive communication, within the curricular designs.The purpose of this study is to identify how conflict resolution methods are preponderant for a harmonious organizational climate from post conflict, from the competences acquired by apprentices in the area of Human Talent Management and their professional practice. The methodology proposes an exploratory - descriptive study with a correlational scope since it hopes to understand the role of human talent managers in the resolution of conflicts in the organization in the current post-conflict.To this purpose, an poll was drafted and implemented for 120 apprentices in and graduates who are working in the area of human talent.